Design improvements in the inner shell of a motorbike helmet using coconut fiber composite - Ariff, Tasnim Firdaus; Jalil, Muhammad Ezurin; Bahar, Rubina (PAK publishing group, 2014)
Composite materials have penetrated into the manufacturing of many items; from domestic commercialized products to automobile and aerospace industries. It has recently been introduced in the making of the outer shell of the motorbike helmet because of its lightweight, strength and high modulus-to-weight ratio properties. This research aims in design improvements in the inner shell of a motorbike helmet using coconut fiber composite. Modelling of the inner shell of the motorbike helmet is done by using CATIA software. Finite Element Analysis (FEA) is used in analysing its performance by using ANSYS software with the determined properties from a series of mechanical testing. The cost analysis of the coconut fiber composite inner shell of the helmet is conducted in this study with the comparison from the cheapest commercial motorbike helmet. The outcome from the mechanical testing shows that this coconut fiber composite is strong with some properties of elasticity in it. This material has shown to have better stress absorption compared to Expanded Polystyrene Styrofoam (EPS). Therefore, this composite can be used as an alternative material to EPS which is non-biodegradable.